Improving Speaking Skills through Small Group Discussion at Eleventh Grade Students of SMA Plus Munirul Arifin NW Praya - Lalu Bohari (Universitas Pendidikan Mandalika, 2020)
This study was aimed at finding the effect of small group discussion in improving speaking skills at the seventh year students of SMA Plus NW. This research was conducted as quasi-experiment using a quantitative approach with One-Group Pretest-Posttest design. The population of the research was the eleventh-grade students of SMA Plus Munirul Arifin NW Praya in academic year 2018/2019. Each class consists of 28 students. The total population was 95 students. In this study, the researcher took one class as a sample. The class was eleventh Grade of MIPA 1 consisting of 28 students as the experiment. The researcher gave treatment to the experimental group and it used Small Group Discussion as the treatment of teaching speaking. The purpose of using the Small Group Discussion was to give new inspiration that can be applied in teaching speaking. Referring to the result pre-test and post-test showed that the sig (2 tailed) > 0.05, it means that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. So the use of Small Group Discussion in teaching speaking is effective. The value of t-test was higher than the t-value of t-table (t-test 8.5148 > t-table 2.006). It showed that teaching speaking using small group discussion has a positive effect to improve students' speaking skill. Besides that, the result of the mean of post-test was higher than the mean of pre-test (M2 = 18.43 > M1 = 14.25). It means that teaching speaking by using small group discussion was more effective than teaching speaking without using small group discussion. In addition, small group discussion can improve students' speaking skill in the eleventh-grade students of SMA Plus Munirul Arifin NW Praya.